A prospective, open-label, single-arm study to evaluate the efficacy of dydrogesterone in the treatment of endometrial polyps. (1st February 2021) - Chen, Qian; Zhang, Da; Wang, Shu; Lang, Jing-He; Chao, Xiao-Pei; Fan, Qing-Bo
Abstract: Object: To evaluate the efficacy of dydrogesterone for the treatment of premenopausal patients with endometrial polyps (EPs). Methods: A single-center, open-label, prospective, single-arm clinical treatment trial was conducted in patients of reproductive age with EP(s). Patients were prescribed dydrogesterone from day 15 to day 24 of the menstrual cycle over a period of 3 months. At the 3-month follow-up, the efficacy of dydrogesterone was evaluated based on changes in self-report symptoms and ultrasonographic characteristics. The predictive factors of efficacy as well as the predictive value of the significant factors were also assessed. Results: A total of 60 patients were included. Improvements in both symptoms and ultrasound findings occurred in 31 patients, achieving an efficacy rate of 51.67%. Of 41 patients with clinical presentations, 39 (95.1%) reported improvements in symptoms. In terms of ultrasound findings, 33 (55%) of patients demonstrated improvements. Significant decreases were observed in the mean endometrial thickness (1.17 ± 0.33 cm vs 0.90 ± 0.35 cm, p < .001) and polyp size (1.10 ± 0.34 cm vs 0.74 ± 0.65 cm, p = .001) after the application of dydrogesterone. Age ( p = .006), polyp size ( p = .006), and blood flow within polyps ( p = .035) were significant predictors of dydrogesterone efficacy. These factors, when combined, demonstrated a good predictive value ([area under the curve (AUC)=0.81]). Conclusion: Dydrogesterone is effective in the management of EPs in premenopausal patients. Age, polyp size and blood flow should be taken into consideration when prescribing dydrogesterone for this population of women.